2017
DOI: 10.1111/ecoj.12512
|View full text |Cite
|
Sign up to set email alerts
|

Two Sides of the Same Rupee? Comparing Demand for Microcredit and Microsaving in a Framed Field Experiment in Rural Pakistan

Abstract: We use a field experiment to test whether saving and borrowing satisfy demand for lump‐sum accumulation from regular deposits. Inspired by ROSCAs, we offer different credit and saving contracts to subjects. We find that individuals often accept both credit and saving contract across experimental waves. This behaviour can be rationalised by assuming that individuals seek lump‐sum payments and struggle to hold savings. Structural estimation of this model accounts for the behaviour of 75% of participants. Of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 49 publications
4
24
0
Order By: Relevance
“…From a policy angle, the demand for infrequent payments may thus have implications for cash transfer design in both poor and rich countries alike (Banerjee, 2016 There is by now abundant evidence that individual preferences are time-inconsistent and that commitment devices help in choices as diverse as saving, effort provision, and smoking 1 Rutherford (2000) documents the importance of lump sums for the poor. Bauer et al (2012) argues that demand for lump sums may drive a correlation between present-biased preferences and demand for microcredit while Afzal et al (2017) argues that it may explain simultaneous demand for saving and credit contracts. Our experimental evidence is consistent with poor households receiving negative interest rates on savings, for instance on deposits to money collectors (Collins et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…From a policy angle, the demand for infrequent payments may thus have implications for cash transfer design in both poor and rich countries alike (Banerjee, 2016 There is by now abundant evidence that individual preferences are time-inconsistent and that commitment devices help in choices as diverse as saving, effort provision, and smoking 1 Rutherford (2000) documents the importance of lump sums for the poor. Bauer et al (2012) argues that demand for lump sums may drive a correlation between present-biased preferences and demand for microcredit while Afzal et al (2017) argues that it may explain simultaneous demand for saving and credit contracts. Our experimental evidence is consistent with poor households receiving negative interest rates on savings, for instance on deposits to money collectors (Collins et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…While the link from entrepreneurship toward savings and wealth concentration has been found in developed countries (Gentry & Hubbard, 2004; Quadrini, 1999), it was now suggested that, inversely, savings may boost entrepreneurship among the poor since it is their principal source of entrepreneurial finance (Gunu, 2010; Lianos & Pseiridis, 2009). Others consider that both microcredit and microsavings are complementary, and a balanced approach is required (Adams & Vogel, 2016) or that they essentially achieve the same purpose since the poor need to make lump sum payments (Afzal, d'Adda, Fafchamps, Quinn, & Said, 2018). In any case, it seems there is considerable demand for microsavings products among the poor (Dupas & Robinson, 2013).…”
Section: Academic Literature On Microsavingsmentioning
confidence: 99%
“…Finance is a source and process of funding. Funding is essential for starting or developing a commercial entity 1 . Money, on the other hand is an instrument of exchange and a store of value in a country.…”
Section: The Idea Of Savings For the Poormentioning
confidence: 99%